Perceptions of Ethics Across Situations: A View Through Three Different Lenses - Carlson, Dawn S. (Journal of business ethics, 1997)
This paper examined three approaches for understanding perceptions of ethics: moral philosophies, cognitive moral development, and ethical value systems. First, the dimensionality of the moral philosophy approach was examined. Next, an attempt was made to integrate the models. Finally, each of the model's various components were used in a regression equation to isolate the best predictors of ethicality. Results indicated that the moral philosophies can be considered distinct entities, but the common underlying theme between the approaches was not as predicted. Also, individuals used a variety of approaches, not always the same ones, to determine the ethicalness of situations.